PENGARUH PENGGUNAAN GAME EDUKASI WORDWALL TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Gina Nurul Walidah; Achmad Mudrikah; Samnur Saputra (Universitas Islam Nusantara, 2022)
This research is motivated by the lack of student motivation to learn, causing student learning outcomes to be low. Alternative media that can be used to increase students' motivation and learning outcomes is wordwall educational game media. The purpose of this study was to determine whether there was a significant effect of the use of wordwall educational games on the motivation and learning outcomes of seventh grade students in the quadrilateral material. This research is a quantitative research with an experimental model. The data collection technique for motivation is a questionnaire, while the data collection for learning outcomes is pretest and posttest. The data analysis technique was carried out using SPSS 19.0 for windows with t-test. The results of this study indicate that the use of wordwall educational games in mathematics learning activities has a significant effect on students' motivation and learning outcomes. It can be seen from the percentage of learning motivation in the experimental class is higher than the control class and the average value of the experimental class is higher than the control class.